The Effect of Word Frequency on Phonemic Accuracy in Children With Cochlear Implants and Peers With Typical Levels of Hearing. (30th May 2017) - Faes, Jolien; Gillis, Joris; Gillis, Steven
Abstract: The frequency of occurrence of words and sounds has a pervasive influence on typically developing children's language acquisition. For instance, highly frequent words appear earliest in a child's lexicon, and highly frequent phonemes are produced more accurately. This study evaluates (a) whether word frequency influences word accuracy and (b) whether this is also the case for children with a history of auditory deprivation. More specifically, the influence of word frequency on phonemic accuracy is examined in deaf children with a cochlear implant (CI), and compared to age-matched children with typical hearing, between word onset and age 7. Results show that highly frequent words are produced more accurately, except for words in the highest frequency regions (i.e., predominantly closed-class words). This effect is more pronounced in children with typical hearing when compared with children with CI. Thus, children with CI are sensitive to word frequency, but to a lesser extent than peers with typical hearing.